2019
DOI: 10.1371/journal.pone.0223468
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cardiac and respiratory inhibition during seizure precedes death in the DBA/1 audiogenic mouse model of SUDEP

Abstract: This study was designed to evaluate cardiac and respiratory dysfunction in a mouse model of sudden unexpected death in epilepsy i.e., SUDEP. We simultaneously monitored respiration via plethysmography and the electrocardiogram via telemetry before, during, and after an audiogenic seizure. DBA/1 mice responded to an acoustic stimulus with one or two cycles of circling and jumping before entering a clonic/tonic seizure. This was followed by death unless the mice were resuscitated by mechanical ventilation using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Also, our model suggests that transient bradycardia following the seizure-induced tachycardia may be due to a massive vagal activation and a sympathetic withdrawal. This results are in accordance with recent animal experiments in the field suggesting that bradycardia preceding SUDEP is due to a significant vagal discharge [13].…”
Section: Resultssupporting
confidence: 93%
“…Also, our model suggests that transient bradycardia following the seizure-induced tachycardia may be due to a massive vagal activation and a sympathetic withdrawal. This results are in accordance with recent animal experiments in the field suggesting that bradycardia preceding SUDEP is due to a significant vagal discharge [13].…”
Section: Resultssupporting
confidence: 93%
“…Comparing the sudden death and long‐lived groups, the authors did not find any significant differences in the arrhythmias produced or malignant rhythm alteration, while marked differences in ventilation were found. 57 , 58 , 59 However, although different studies evidenced that respiratory dysfunction could be the first alteration in SUDEP and precede cardiac involvement, 54 , 55 data are still conflicting, and further research is needed to clarify the physiopathology of SUDEP.…”
Section: Cardiac Changes In Sudepmentioning
confidence: 99%
“…Although cases of SUDEP point to cardiac causes, particularly undiagnosed cardiac channelopathies, the majority appear to be linked to the disruption of certain brain structures associated with autonomic control of the cardiorespiratory function due to epilepsy (Manolis et al., 2019). In a mice model study of SUDEP which was induced by audiogenic seizures, tonic‐clonic seizures had caused sudden and simultaneous respiratory and cardiac depression (Schilling et al., 2019). Although the endpoint death was resulted from respiratory arrest, the study showed that the seizure activity activated two central nervous system pathways in this model, where one of them inhibits the respiratory drive, while the other one inhibits cardiac function through vagal afferents (Schilling et al., 2019).…”
Section: Cardiorespiratory Findingsmentioning
confidence: 99%